First Occurrence of Eudiplozoon Kamegaii Nishira & Urabe, 2020 (Monogenea: Diplozoidae) in Iraq from Gills of Common Carp Cyprinus Carpio - Mohammed Salih Abboud, Kefah Naser Abdul-Ameer (Pakistan Journal of Medical & Health Sciences, 2022)
In this study, the monogenean Eudiplozoon kamegaii Nishihira & Urabe, 2020 which is the second species of the genus Eudiplozoon Khotenovsky, 1985 described in the world, was recorded for the first time in Iraq from the gills of the common carp Cyprinus carpio Linnaeus, 1758 which were collected from the Tigris river in the Al-Rashidiya region north of Baghdad province from August 2021 until May 2022. The description and measurements of this parasite, as well as its illustrations, were given.